Principios y reglas de las decisiones de la política criminal (Persona y Derecho, 2018)
This submission proposes that Criminal Policy decisions (legislation, judicial rulings and Government regulation) can achieve a certain degree of stability. Stability renders the decision making process reasonable, by virtue of its modality of rational argumentation guided by principies, rules, exceptions and "meta-rules". This stability makes possible comprehension, consensus, rational critical analysis, and the gradual improvement of the decisions.